Investigating the Possibility and Effects of Arbitration Term in the Statute of Commercial Firms - Afarin, HamidReza (2021)
Arbitration is carried out based on the parties’ agreement, outside official authorities. As a result, it is carried out faster, at a lower price, and based on the confidence of the both parties in the arbitrator(s). The ways to include arbitration term in the statute of commercial firms include stating in the contract, stating in the statute, and stating in other commercial documents such as articles of partnership and primary corporation agreement. The conditions of validity of including arbitration term in the statute of commercial firms are the same as essential trading terms pointed to in the article 190 of the civil code. Cases in which including the arbitration term in the statute of commercial firms is prohibited include bankruptcy related disputes, which based on the article 496 of the civil procedure code (2001) cannot be settled through arbitration. This is because bankruptcy is a matter of public order. In addition, there are doubts whether arbitration term can be included in the statute of commercial firms in cases of certain disputes such as termination, nullity and in general, company-dissolution-disputes. This is also because in terms of effects, company dissolution is similar to bankruptcy, leaving the task of determining a settlement manager to the court instead of arbitrators.